Skalendokumentation des Projekts EFBI Einstellungen von FSJler*innen zu Behinderung und Inklusion - Willems, Ariane S. (Universitätsverlag Göttingen, 2021)
This volume documents the survey instruments used in the project "Attitudes of FSJ volunteers towards disability and inclusion" (EFBI). The EFBI project investigated how attitudes towards inclusion and (people with) disabilities develop over the course of a voluntary social year and which personal and context-related characteristics are associated with this.In the first part of the scale documentation for the EFBI project, the authors provide information about the background, goals and design of the project and in the second part present the questionnaires used to record attitudes towards disability and inclusion as well as personal and context-related characteristics in a standardized way at the beginning, middle and end of the voluntary social year. Translated with www.DeepL.com/Translator (free version)